The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7717/peerj.15954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drought stress level in Sargent’s cherry (Prunus sargentii Rehder) using photosynthesis and chlorophyll fluorescence parameters and proline content analysis

Eon Ju Jin,
Jun-Hyuk Yoon,
Hyeok Lee
et al.

Abstract: Sargent’s cherry trees (Prunus sargentiiRehder) are widely planted as an ornamental, climate change-sensing species. This study investigated changes in the soil moisture content, fresh weight, photosynthesis and chlorophyll fluorescence properties, and the chlorophyll and proline content of four-year-old P. sargentii seedlings after 30 days of drought stress. In the trees subjected to drought stress treatment, soil moisture content decreased, and the fresh weight of the aboveground part of the plant decreased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Therefore, the recovery of Pn can be attributed to the regulation of Gs by 5-NGS, which maintains the supply of CO 2 and replenishes the raw material for photosynthesis. The inhibition of photosynthetic capacity by drought stress is also manifested in damage to the photosystems and degradation of photosynthetic pigments ( Jin et al, 2023 ). Our results showed that SPAD levels were reduced under the osmotic stress treatments compared to those in the control, and F v /F m decreased, resulting in the inhibition of PSII ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the recovery of Pn can be attributed to the regulation of Gs by 5-NGS, which maintains the supply of CO 2 and replenishes the raw material for photosynthesis. The inhibition of photosynthetic capacity by drought stress is also manifested in damage to the photosystems and degradation of photosynthetic pigments ( Jin et al, 2023 ). Our results showed that SPAD levels were reduced under the osmotic stress treatments compared to those in the control, and F v /F m decreased, resulting in the inhibition of PSII ( Figs.…”
Section: Discussionmentioning
confidence: 99%